2017
DOI: 10.1111/aas.12907
|View full text |Cite
|
Sign up to set email alerts
|

Objective neuromuscular monitoring of neuromuscular blockade in Denmark: an online‐based survey of current practice

Abstract: In this survey, Danish anaesthetists frequently, in an international perspective, use objNMM, but the use is often associated with technical difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The Danish general anesthesia guideline from 2017 states that a nerve stimulator should be used whenever a nondepolarizing muscle relaxant is administered [76]. Despite not calling for quantitative monitoring, Denmark has an advanced monitoring practice that involves quantitative monitoring [41,51,77]. A survey in 2017 showed that 58% of the 653 responding anesthesiologists always use objective monitoring and 86% in at least three quarter of their patients.…”
Section: Specialty Society Guidelines and International Panelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Danish general anesthesia guideline from 2017 states that a nerve stimulator should be used whenever a nondepolarizing muscle relaxant is administered [76]. Despite not calling for quantitative monitoring, Denmark has an advanced monitoring practice that involves quantitative monitoring [41,51,77]. A survey in 2017 showed that 58% of the 653 responding anesthesiologists always use objective monitoring and 86% in at least three quarter of their patients.…”
Section: Specialty Society Guidelines and International Panelsmentioning
confidence: 99%
“…A survey in 2017 showed that 58% of the 653 responding anesthesiologists always use objective monitoring and 86% in at least three quarter of their patients. Nearly all (97%) of the respondents reported having access to objective monitors [41].…”
Section: Specialty Society Guidelines and International Panelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple surveys conducted worldwide indicate that neuromuscular blocking drugs and their antagonists are commonly administered without adequate rationalization and monitoring, leading to variable incidence of RNMB. Studies from the United States, Europe,[6] Australia and New Zealand,[78] Italy,[910] Denmark,[11] Morocco,[12] and Brazil[13] suggest that currently, only a small percentage of anesthesiologists monitor neuromuscular function in their clinical practice, even in special patient groups. In addition, the absence of internationally accepted clinical guidelines regarding neuromuscular blockade remains a major problem.…”
Section: Introductionmentioning
confidence: 99%